Современные радиолокационные методы исследования метеорных явлений с использованием сторонних источников излучения и перспектывы их развития - Стародубов, Р. К. (ХНУРЭ, 2012)
At the present time to study ttie ettects ot meteor is widely used radar method with using external radiation sources. With transition from analog to digital broadcasting the type of signal will be changed. Objective of this work is to evaluate the potential use of digital TV signals to study the effects of meteor.